The influence of role conflict, supervisor support and physical work environment on job burnout among hotel chefs in Malaysia - Abdul Hadi, Arnieyantie; U.Z.A, Ungku Fatimah; M.N, Norfezah; G., Hazrina (Universiti Teknologi MARA, 2022)
The output quality can portray the complexity of the chef's work nature in the hospitality industry in a demanding service environment. Frequently facing inconsistent demand and lack of supervisor support results in chefs likely being confronted with role conflict. Working in an unfavorable physical environment has exposed the chef to job burnout. As the job burnout phenomenon has been scarcely studied in the Malaysian hospitality context, this study aims to investigate the relationship of variables using the Job Demand Resources (JD-R) model as a foundation focusing on emotional exhaustion (EE) as the first dimension of burnout. A quantitative method approach was applied through a self-administered survey involving 440 chefs. The result showed that role conflict and physical work environment significantly influences emotional exhaustion (p<0.05), while supervisor support does not influence the exhaustion of chefs. Each factor has acceptable internal reliability (Cronbach α = 0.7-0.9) and confirmatory factor analysis result provided evidence for convergent (Overall factor loading>0.6, AVE>0.5, CR>0.7) and discriminant validity (HTMT ratio <0.90). The result of structural equation modeling found the proposed model predictive of emotional exhaustion (R2 = 0.194, Q2 = 0.107). It can be concluded that chefs responsible for many duties at a time and working in unfavorable environments tend to experience emotional exhaustion that can lead to other dimensions of job burnout. On the other hand, the positive support from the supervisor results in less stress for the chefs. The findings can assist the head of the chef in improving their system, especially on the job description and task delegation to overcome conflict. At the same time, management can focus on significant variables to combat the cause that may lead to job burnout within a hotel kitchen setting.